Personality Traits and Employment : BIBB-Follow-up Survey to the 2018 BIBB/BAuA Employment Survey - Rohrbach-Schmidt, Daniela [Verfasser]; Krüger, Sabine [Verfasser]; Ebner, Christian [Verfasser] (Bundesinstitut für Berufsbildung, 2020)
"Empirical studies show that various dimensions of personality such as extraversion or neuroticism, but also specific behaviour-related personality traits and preferences such as risk taking, self-efficacy and locus of control are related to characteristics of employment and career success. Personality traits are not surveyed in the 2018 Employment Survey conducted by the Federal Institute for Vocational Education and Training (BIBB) and the Federal Institute for Occupational Safety and Health (BAuA) - ETB 2018 for short. In a follow-up survey, 8.010 core employed persons who participated in the ETB 2018 were therefore asked about their personality traits and took part in a vocabulary test. The data linked from both interviews can be used to investigate various questions, such as the connection between personality traits and career success." (BIBB-Doku1)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; BIBB-/BAuA-Erhebung; Berufserfolg; Erwerbstätigkeit; Persönlichkeitsmerkmal; Einflussfaktor